linguistic Experimentation In The Narrative Poem "the Ballad Of Love And Blood" By Ezzedine Djlaoudji - bechelaleg, leila; khelouf, Meftah (El Omda in Linguistics and Discourse Analysis, 2025)
Fields of life have witnessed rapid transformations imposed by the postmodern era. Since culture is a part of life, and literature is a part of this culture, it too has experienced a wave of transformations and developments. As a result, those working in the field of literature have attempted to transcend the ordinary in a way that aligns with the audience's taste, leading to the emergence of new critical terms such as gender crossing, genre blending, and integration, all of which fall under the umbrella of what is termed experimentation. The latter aims to break the conventionality of literary texts and seek new techniques that bet on the openness between sciences. The theater was not immune to the phenomenon of experimentation by breaking away from the norm and presenting alternative ideas. The Algerian theater, too, did not escape the realm of experimentation, which became evident in the theatrical works of Abdelkader Alloula and Wuld Abdel Rahman Kaki, culminating in the efforts of Azeddine Glaoui. We will attempt through this study to shed light on the narrative Poem, and then we will work on identifying the manifestations and mechanisms of linguistic experimentation in the narrative Poem "The Song of Love and Blood."